Effect of Adding Beet Puree (Beta vulgaris L) on the Characteristics of Dry Noodles Made from Wheat Flour with Substitution of Sorghum (Sorghum bicolor (L) Moench) Flour - Sylvi, Diana; Hari, Purnama Dini; Asma, Fadhillawati Fri (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
This study aims to determine the effect of adding beet tuber puree on the characteristics of dry noodles made from wheat flour with sorghum flour substitution. This research design used Complete Randomized Design (CRD) with 5 treatments and 3 repeats. The treatments carried out in this study were A (Control), B (Addition of beet tuber puree 3%), C (Addition of beet tuber puree 6%, D (Addition of beet tuber puree 9%), and E (Addition of beet tuber puree 12%). The data obtained in the study were carried out statistical analysis by ANOVA then continued with the analysis of Duncan's New Multiple Range Test (DNMRT) at the level of 5% effect on water content, ash content, protein content, fat content, carbohydrate content, antioxidant activity, color, and elasticity The best treatment based on physical, chemical, and organoleptic properties is treatment E (addition of puree 12%) with moisture content. of 8.89%, ash content of 2.83%, protein content of 13.58%, fat content of 2.80%, carbohydrate content of 71.89%, elasticity of 57.27%, value of 78.57 â¸°hue (yellow-red) and total plate count of 0.79 x 105 CFU/ml, organoleptic analysis color 4.65 (likes), aroma 4.15 (likes), texture 4.30 (likes), and taste 3.90 (regular).